A Potency and Challenge in Implementation of Warehouse Receipts System (WRS) in Niaga Mukti Cooperative, Cianjur - Khasanah, Ukhwatul; Hadi, Dwijono; Hartono, Slamet (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2018)
The aims of this study are to analyze and describe the potency and challenge in implementation of warehouse receipts system in Niaga Mukti Cooperative, Cianjur. The used method is descriptive analysis with the subject of Niaga Mukti Cooperative as the sample of WRS for rice commodity. The result of the research tells that warehouse receipts system has potency as collateral credit document to obtain the finance of farm for the member of Niaga Mukti Cooperative with 6% per year or 1,5% per month after obtaining from the government grant. In conducting WRS program, the cooperative confronts various challenges such as empowering of economic society through WRS, empowering of warehouse receipts as alternative finance, finance instruments and marketing for farm and requiring coordination and correlation among the government, regions, farm cooperative, bussinessmen, and finance institutions.